Vertical Transmission of COVID-19: A Case Report and Review of Literature - Thapa, Bibechan; Acharya, Sharda; Karki, Shreyasi (Journal of Nepal Health Research Council, 2021)
Coronavirus disease 2019 (COVID-19) pandemic will continue affecting pregnant women with possibility of vertical transmissions. However, knowledge and evidences regarding vertical transmission of COVID-19 are just emerging. This information is very crucial in the obstetrical care of COVID-19 infected women as well as in the care of newborn born to COVID-19 positive mothers. We report a case of vertical transmission in a neonate born to asymptomatic COVID-19 infected mother. Newborn was immediately shifted to isolation nursery and formula feed was started. The nasopharyngeal swab of newborn taken at 42 hours of life tested positive for SARS-CoV-2 by RT-PCR. Therefore the vertical transmission in COVID-19 is possible. Despite this, the neonatal outcome is good. Keywords: Duodenal atresia; flip flop circulation; neonates; persistent pulmonary hypertension of newborn